2013
DOI: 10.1084/jem.20120662
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency for endoglin in tumor vasculature weakens the endothelial barrier to metastatic dissemination

Abstract: Genetic deficiency for endoglin leads to increased metastatic capability by weakening the endothelial cell barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 70 publications
4
104
2
9
Order By: Relevance
“…In addition, when we analyzed the expression pattern of Pdgfd during tumorigenesis in RIP1-TAg2 mice, we found Pdgfd to be significantly up-regulated in angiogenic islets, compared with other stages of normal or malignant islets (Fig. 1B), an expression pattern previously found to be characteristic for genes expressed by ECs (13). Next, we generated a mouse line in which the Pdgfd exon 1 was substituted for a LacZ reporter cassette, allowing for monitoring of gene expression by X-gal staining.…”
Section: Significancesupporting
confidence: 52%
“…In addition, when we analyzed the expression pattern of Pdgfd during tumorigenesis in RIP1-TAg2 mice, we found Pdgfd to be significantly up-regulated in angiogenic islets, compared with other stages of normal or malignant islets (Fig. 1B), an expression pattern previously found to be characteristic for genes expressed by ECs (13). Next, we generated a mouse line in which the Pdgfd exon 1 was substituted for a LacZ reporter cassette, allowing for monitoring of gene expression by X-gal staining.…”
Section: Significancesupporting
confidence: 52%
“…Endoglin was reported as an inhibitor of EndMT in ECs and the deficiency of endoglin in ECs could promote EndMT in tumor vasculature 34. We examined whether miR‐342‐5p might promote EndMT.…”
Section: Resultsmentioning
confidence: 99%
“…Although endoglin functions as a coreceptor of TGF‐β signaling, this molecule has been shown to inhibit some pathways downstream from TGF‐β receptors 20, 21. Indeed, Anderberg et al recently showed that deficiency in endoglin resulted in tumor vasculature that displayed hallmarks of EndMT 34. Our results indicated that miR‐342‐5p repressed the expression of endoglin through its 3′ UTR; therefore, it is likely that miR‐342‐5p promoted EC migration by inhibiting endoglin, leading to enhanced EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…Gene microarray data from different stages of melanoma progression were analyzed and shed light on the mechanism of metastasis [55][56][57][58]. Metastatic tumor cells in circulation have been long recognized, and CTCs in the blood stream have been successfully isolated from human blood [59][60][61]. An FDA approved detection system, Cellsearch, is available for the isolation of CTCs and has been successfully used for monitoring patients with metastatic breast, prostate and colon cancers [62].…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, two groups showed strong evidence that Snail1 binds directly to the promoter of E-cadherin and represses the transcription of this gene in invasive mouse and human carcinoma cell lines [57,58]. Other Zn (zinc)-finger transcription factors, including Snail2 [59], ZEB1 [60], ZEB2 [61], were also shown to directly bind to the E-boxes of the E-cadherin promoter to repress its transcription. In addition to these Zn-finger transcription factors, ectopic expression of bHLH family transcription factor Twist1 resulted in the loss of E-cadherin mediated cell-cell adhesion, expression of mesenchymal markers and induction of cell motility, hallmarks of EMT in normal mammalian cells.…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%